5 essential mental skills for sport - Archer, Mark; Gould, Daniel; Virtual Brands; Del Padre Visual Productions ([Wilbraham, Mass.] : Virtual Brands, 2001)
Sport psychology consultant, Daniel Gould, shares drills and exercises that help to develop mental skiils essential to achieve success. The five skills include: motivation, positive thinking, confidence, emotional energy management, and mental preparation
Title from title screen
Executive producers: Britt Brewer, Al Petitpas, Judy Van Raalte ; camera, Geoff Alson, Mark Archer, Wendy Wong
Consultant: Daniel Gould
Keywords: Sports -- Psychological aspects; Athletes -- Psychology